2021
DOI: 10.4102/sajhrm.v19i0.1409
|View full text |Cite
|
Sign up to set email alerts
|

Understanding intention to quit amongst artisans and engineers: The facilitating role of commitment

Abstract: Orientation: Given the critical shortage of skilled artisans and engineers in the job market, retention of this key talent is of paramount importance.Research purpose: The aim of this study was to identify the determinants of affective commitment and investigate the impact thereof on intention to quit (ITQ) amongst artisans and engineers.Motivation for the study: For human resource management interventions to be effective in retaining artisans and engineers, the constructs underlying commitment and stay intent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 88 publications
1
3
0
2
Order By: Relevance
“…This suggests that OC improves performance and minimizes turnover; hence, organizational commitment is based on fulfilling employees' wants and desires. Investigation from the researchers revealed that employees who are not committed to their organization, according to the social exchange theory (SET), are more likely to reciprocate by exhibiting unfavorable behaviors toward the organization (Deeprose, 2018;Siwela & van der Bank, 2021). This suggests that many factors affect OC (Chanana, 2020).…”
Section: Workplace Ostracism Among Bank Employeesmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that OC improves performance and minimizes turnover; hence, organizational commitment is based on fulfilling employees' wants and desires. Investigation from the researchers revealed that employees who are not committed to their organization, according to the social exchange theory (SET), are more likely to reciprocate by exhibiting unfavorable behaviors toward the organization (Deeprose, 2018;Siwela & van der Bank, 2021). This suggests that many factors affect OC (Chanana, 2020).…”
Section: Workplace Ostracism Among Bank Employeesmentioning
confidence: 99%
“…Therefore, it has been shown that workplace ostracism reduces discretionary behavior and increases unproductive work behavior, and reduces organizational commitment (Zhao & Xia, 2017). The onus is on the manager to inculcate an attitude of high commitment in employees by discouraging the aforementioned attitudes to foster the manifestation of low absenteeism, more punctuality at work, being goal-oriented and relatively good productivity (Siwela & van der Bank, 2021).…”
Section: Workplace Ostracism Among Bank Employeesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studi sebelumnya menunjukkan bahwa job insecurity memiliki dampak negatif terhadap affective organizational commitment (e.g., Chirumbolo et al, 2017;Jiang & Lavaysse, 2018;Stankevičiūtė et al, 2021). Penelitian lainnya telah membuktikan adanya pengaruh negatif affective organizational commitment terhadap turnover intention (e.g., Els, Brouwers & Lodewyk, 2021;Yan et al, 2021;Živković et al, 2021;Siwela & Van, 2021;Murray & Holmes, 2021). Selanjutnya, terdapat penelitian yang membuktikan bahwa affective organizational commitment dapat menurunkan tingkat turnover intention (e.g., Els et al, 2021;Yan et al, 2021;Živković et al 2021;Siwela, 2021;Murray & Holmes, 2021).…”
Section: Jobunclassified
“…Penelitian lainnya telah membuktikan adanya pengaruh negatif affective organizational commitment terhadap turnover intention (e.g., Els, Brouwers & Lodewyk, 2021;Yan et al, 2021;Živković et al, 2021;Siwela & Van, 2021;Murray & Holmes, 2021). Selanjutnya, terdapat penelitian yang membuktikan bahwa affective organizational commitment dapat menurunkan tingkat turnover intention (e.g., Els et al, 2021;Yan et al, 2021;Živković et al 2021;Siwela, 2021;Murray & Holmes, 2021). Studi sebelumnya menjelaskan bahwa job insecurity memiliki pengaruh negative pada work engagement (e.g., Jiang & Lavaysse, 2018;Stankevičiūtė et al, 2021).…”
Section: Jobunclassified